Revisiting the Organismic Valuing Process Theory of Personal Growth: A Theoretical Review of Rogers and Its Connection to Positive Psychology - Maurer, Mia M.; Daukantaitė, Daiva (Frontiers in Psychology, 2020)
Humanistic and positive psychology have had a contentious past. Initially, positive psychology researchers have distanced themselves from humanistic psychology, proceeding to build an array of differentiated constructs relevant to an empirical study of well-being. Twenty years on, it is now generally acknowledged that humanistic psychology is the theoretical predecessor of positive psychology in terms of holistic growth theories. In this theoretical review, we aim to show how Carl Rogers’ organismic valuing process (OVP) theory can serve as a holistic framework for individual positive psychological research findings and theories, and how, positive psychology, in turn, provides empirical support for this meta-theoretical framework. An important motivation for considering personal growth as a process that integrates various aspects of well-being is theoretical integration, which can help us better understand how well-being develops in individuals across the lifespan. Some theoretical and practical implications of incorporating OVP theory into well-being research are also suggested.